2017
DOI: 10.1063/1.4976577
|View full text |Cite
|
Sign up to set email alerts
|

Portable pyroelectric electron probe microanalyzer with a spot size of 40 μm

Abstract: We report a method of reducing the spot size of an electron beam in a portable pyroelectric electron probe microanalyzer (EPMA) and its application to on-site microanalysis. An electron beam with a spot size of 40 μm full width at half maximum was achieved by preventing the production of an electric field on the side of a needle tip set on the pyroelectric crystal in the EPMA by coating the side of the tip with an insulating material. This spot size was approximately 10 times smaller than that previously repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Comparing MgAl 2 O 4 spinel and Al 2 O 3 particles with similar size, such as particles 1 and 4, it could be shown that the XEOL intensity of MgAl 2 O 4 spinel is higher than that of Al 2 O 3 . This trend is consistent with the results that we have previously obtained by investigating the CL spectra of a single particle with the size of approximately 100 μ m consisting of MgAl 2 O 4 spinel and Al 2 O 3 phases; the CL intensity of MgAl 2 O 4 spinel was ~10 times higher than that of Al 2 O 3 (Imashuku & Wagatsuma, 2017). Thus, when we used the digital single-lens reflex camera, the number of particles producing green luminescence was larger than that of particles producing blue luminescence, as shown in Figure 2b, although almost the same amounts of MgAl 2 O 4 spinel and Al 2 O 3 were present in the model sample.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Comparing MgAl 2 O 4 spinel and Al 2 O 3 particles with similar size, such as particles 1 and 4, it could be shown that the XEOL intensity of MgAl 2 O 4 spinel is higher than that of Al 2 O 3 . This trend is consistent with the results that we have previously obtained by investigating the CL spectra of a single particle with the size of approximately 100 μ m consisting of MgAl 2 O 4 spinel and Al 2 O 3 phases; the CL intensity of MgAl 2 O 4 spinel was ~10 times higher than that of Al 2 O 3 (Imashuku & Wagatsuma, 2017). Thus, when we used the digital single-lens reflex camera, the number of particles producing green luminescence was larger than that of particles producing blue luminescence, as shown in Figure 2b, although almost the same amounts of MgAl 2 O 4 spinel and Al 2 O 3 were present in the model sample.…”
Section: Resultssupporting
confidence: 92%
“…Cu L, Si K, and Cu K lines were detected in both spectra. The Si K line was attributed to the insulating materials coated on the Pt 0.8 Ir 0.2 wire and the needle holder (Imashuku & Wagatsuma, 2017). The characteristic X-rays of copper (Cu L and Cu K) originated from copper in the model sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the accumulated 10 pulses, the detection limits to Na and Mg elements reach 2-100 ppm, while the detection limits to elements such as Cu, Si, Ni, Mn, Fe, Al are generally 0.01%-2% [1][2][3][4][5] . Electron beam microanalysis [6][7][8] is the most commonly used microanalysis technology in the world. Representative of them are electron probes or scanning electron microscope X-ray energy spectrum analyzers, although it can give detailed chemical composition information, it is only suitable for the analysis of small-area samples.…”
Section: Introductionmentioning
confidence: 99%